Pengaruh Kepemimpinan Kepala Sekolah dan Lingkungan Kerja Terhadap Kinerja Guru Di Gugus 1 Balikpapan Barat - Elisabeth Yusnita; Maria Goreti Rini Kristiantari; Tita Rosita (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to analyze the influence of principal leadership and work environment on teacher performance in Cluster 1, West Balikpapan. A quantitative approach with an explanatory survey design was employed. The respondents consisted of 40 teachers selected from a population of 87 teachers in the school cluster. Data were collected through questionnaires that had passed validity and reliability tests and were analyzed using multiple linear regression with SPSS after the classical assumption tests were conducted. Hypothesis testing used t-tests for partial effects and an F-test for simultaneous effects. The findings revealed that principal leadership had a positive and significant effect on teacher performance (β = 0.484; sig. = 0.006), contributing 23.4% to teacher performance variation. The work environment also had a positive and significant effect (β = 0.469; sig. = 0.008), contributing 22.0%. Simultaneously, principal leadership and work environment significantly influenced teacher performance (F = 136.120; sig. = 0.000). The coefficient of determination (R Square = 0.855) indicated that both variables explained 85.5% of the variation in teacher performance, while 14.5% was influenced by other factors. These findings show that effective school leadership and a supportive work environment are important conditions for strengthening teacher performance in primary schools.